The Concept of War in Wilfred Owen’s Poetry - Abdalla Fatah Balu; Shwana Qadir Perot (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This paper explores the concept of war in Wilfred Owen’s poems to familiarize readers and scholars with the most considerable concerns that were concentrated by the poet in his terrible experience in World War I. It consists of various sections, in which a critical analysis of each part is given. In its introduction, a general literary overview of Owen and a historical background of the First World War are focused on the first half of the 20th century which influenced his writing style and subject matter. Then, the idea of pity of war in the body of the paper is discussed as a result of his participation that let him feel all the disastrous consequences the war brought to the life of soldiers in the front and all people in the countries. This shaped and developed his effectual war poetry to warn the people about the reality of war which can be analyzed as his major aim in composing poetry. In addition, special attention is devoted to his concern about revolting against the glory of war and patriotism in another section. For that, his great poems such as ‘Strange Meeting’, ‘The Disabled’, and ‘Dulce et Decorum Est’ are taken into consideration to find his prominent features practically. In conclusion, the main critical characteristics of Owen’s war poetry about the pity of war, rejecting the glory of war, and his depiction of the reality of war is summarized to guide readers to keep the most influential ones in mind.